Perancangan Sistem Informasi Pengelolaan Arsip Duplikat STNK Berbasis Web Menggunakan Metode Prototype - Risti, Risti Risfiani; Budiman, Tedi Budiman (Masoem University, 2025)
Management of duplicate STNK archives at the Garut Police Traffic Unit is currently performed manually. This slows down archive searches, increases the risk of document loss, and leads to inefficient data recapitulation. This research creates a web-based information system for managing duplicate STNK archives, designed to meet the operational needs of the police force. The prototype method was implemented through iterative steps, including needs analysis, rapid design, system development, and user assessment. Functional evaluation was conducted through black box testing involving administrative staff. The testing demonstrated that all key system features functioned 100% successfully. These features include user authentication, STNK duplicate application data management, admin management, data filtering, and PDF report printing. The implementation of this system has been proven to improve archive order, accelerate data retrieval, and support the digitization of Traffic Unit administrative services as part of e-government implementation.